2017
DOI: 10.1111/bjet.12569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of video‐based flipped class instruction on subject reading motivation

Abstract: Video-based flipped class instruction can strengthen the learning motivation of students. The effectiveness of flipped class instruction on teaching effectiveness and subject satisfaction has been evaluated previously. The present study aims to examine the impact of two aspects of subject reading motivation. A total of 100 secondary school students were recruited from 4 classes of 25 students (ie, video-based flipped Mathematics class, traditional Mathematics class, video-based flipped Liberal Studies (LS) cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 21 publications
11
77
0
21
Order By: Relevance
“…Experts in this area of knowledge such as Lee, Park, and Davis (2018) consider that all the singularities that flipped learning embraces, signify a great motivational incentive among students, as they have to play new roles and accomplish technology-based tasks. This leads to a proactive mind-set towards the learning process, enhancing enthusiasm and motivation levels in the students' daily chores (Shih & Tsai, 2017;Tse, Choi, & Tang, 2019), especially in those students who are used to a traditional methodological approach Huan (2016).…”
Section: The State-of-the-art In Flipped Learning In Scientific Litermentioning
confidence: 99%
“…Experts in this area of knowledge such as Lee, Park, and Davis (2018) consider that all the singularities that flipped learning embraces, signify a great motivational incentive among students, as they have to play new roles and accomplish technology-based tasks. This leads to a proactive mind-set towards the learning process, enhancing enthusiasm and motivation levels in the students' daily chores (Shih & Tsai, 2017;Tse, Choi, & Tang, 2019), especially in those students who are used to a traditional methodological approach Huan (2016).…”
Section: The State-of-the-art In Flipped Learning In Scientific Litermentioning
confidence: 99%
“…The student can access the didactic contents, provided that he or she has a mobile device with Internet access, from anywhere and at any time [22,23]. This allows student to adapt the content to his or her learning style or moments of greatest motivation during the training process [24][25][26][27]. In this way, mixed education is promoted, which allows one to combine the best of face-to-face teaching and online teaching [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show the benefits of this teaching method for students. Among these benefits, it has been found that it promotes high motivation rates [27], commitment [30,31], responsibility, and participation [32]. These levels are justified by the high degree of freedom available to students to restructure and adapt the acquisition of theoretical content [21,33] and self-regulate their own training processes [1,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, we observe that the findings have been achieved through traditional formative action, as has happened in this study. In particular, all attitudinal academic indicators such as motivation [40,41,53,54,57], autonomy [22,23,37,38,52,58], collaboration [28,29,[31][32][33]60], participation [34,[62][63][64], problem solving [24,25,35,36], and class time [30,59] have presented analogy with other reported studies of scientific literature, as reflected.…”
Section: Discussionmentioning
confidence: 62%
“…This encourages learning facilitated by technology that has an effect on increasing motivation. Not only does ICT enhance motivation, they also produce the new active role of protagonist for the student, and the change in the daily routine of the student, who is no longer a simple receiver of information, increases the available time for practical tasks, collaboration, and teamwork to solve problems in the classroom [40,41]. All these described benefits and actions for the condition for results of the grades obtained by students that are increased with this innovative methodology due to all the previous work that was done [42,43].Flipped learning has become a fundamental approach for the development of good teaching action based on the technopedagogical use of ICT [44].…”
mentioning
confidence: 99%